Hubungan Kebersihan Gigi dan Mulut dengan Karies Gigi pada Siswa SMPN 2 Bukittinggi Kecamatan Guguk Panjang - Anses Warman; Arnetty Arnetty; Ika Ifitri; Alsri Windra Doni; Aprizal Ponda; Dewi Susanti; Renita Eka Zurianti (Poltekkes Kemenkes Padang, 2025)
Dental caries is a disease that damages hard tooth tissue due to bacterial activity in the oral cavity which breaks down carbohydrates into acids, resulting in demineralization of hard tooth tissue which causes cavities. There are many factors that cause the process of dental caries, one of which is poor dental and oral hygiene because dental and oral hygiene is directly related to the occurrence of dental caries. The aim of the research was to determine the relationship between dental and oral hygiene and dental caries in students at SMPN 2 Bukittinggi. The research method is quantitative with an analytical research design and a cross sectional approach. The research population of all SMPN 2 Bukittinggi students was 920 students and the research sample was 240 students from class VII and VIII using a sampling technique, namely simple random sampling. The research results obtained from the Chi-square test show a p-value of 0.048, so the p-value is smaller than the alpha value (0.05). The conclusion of this study is that there is a significant relationship between dental and oral hygiene and dental caries in students. It is recommended for students at SMPN 2 Bukittinggi to maintain oral hygiene by brushing their teeth twice a day, reducing consumption of sticky sweet foods and carrying out routine dental and oral examinations once every six months to avoid dental caries and other dental and oral diseases.